Heartbreak: A case of post‐infarction cardiogenic shock. Issue 1 (11th January 2019) - Mukherjee, Ashes; Fong, Jason
Abstract: Ventricular septal rupture is a rare but catastrophic complication of acute myocardial infarction. Although it has declined in incidence since the introduction of percutaneous coronary intervention, there hasn't been a significant change of mortality from the condition. In the chain of survival, prompt diagnosis and definitive surgery form the cardinal links. Prolonged medical management is not a feasible option as it is likely to be futile but the aim should be to reduce afterload with the help of intra‐aortic balloon pump or support with ventricular assist devices. Echocardiography sits at the heart of the diagnosis of this time critical condition and will guide accurate therapy and intervention. We present the first reported case from an Australian emergency department, where the echocardiography done by the emergency physician clinched the diagnosis. We emphasise here the paramountcy of emergency physicians being proficient in basic echocardiography to achieve rapid diagnosis. Once diagnosed it is critical to have an individual case‐tailored multi‐disciplinary discussion between emergency medicine, cardiothoracic surgery, cardiology and intensive care as to plan the optimal timing of surgery.